Analysis of Important Factors of Groundwater Availability in Narmada District, West Lombok Regency, West Nusa Tenggara Province - Anita Dwi Indaryani; Dwi Nugroho Wibowo; Erwin Riyanto Ardli; Endang Hilmi; Muslihudin; Syamsul Hidayat; Nazario Gomes (Postgraduate, University of Mataram, 2025)
Groundwater utilization in Narmada Regency has increased significantly while its availability is decreasing. This requires management to maintain clean water supply. Research on variables that affect groundwater availability and interactions between them therefore needs to be carried out. Firstly, a Focused Group Discussion (FGD) was held to identify the variables considered important in groundwater management. Respondents then filled out a set of questionnaires expressing their perceptions about the importance of these variables. The variables were grouped into four dimensions namely Input, Output, Domestic Output and non-Domestic Output. Next, respondents' responses were analyzed using the MICMAC structural analysis tool to sort out variables regarding their influence and dependence as well as evaluating the interactions that occured between the variables. The results showed that there are 7 key variables i.e. Central Government Regulations (PPP). Local Government Regulations (PPD), Rainfall (HUJ), Groundwater Basin (CAT), Forest (HUT), Climate (IK), Number of Population (JP) and 1 regulatory variable ie. Geological variable (GEO) in the groundwater availability system in Narmada District. Also, there exist structured and systematic interactions between dimensions in the system. The results of this study are useful as input in making appropriate regulations for sustainable groundwater in the study area.